PARTIAL PURIFICATION AND CYTOTOXIC ACTIVITY OFL-ASPARAGINASE ISOLATED FROM Escherichia coli - Abbas, Ayat; Sabbah, Majeed; Kathum, Omer (Iraqi Journal of Science, 2024)
L-Asparaginase (E.C.3.5.1.1) is an important natural product that possesses abroad spectrum of antitumor activity. In the present study, L-asparaginase partiallypurified from local isolate of Escherichia coli that were grown aerobically for fourhours and anaerobically for 18hrs on M9 medium contain L-asparagine as solenitrogen source. Extraction of the enzyme was done by sonication. Qualitative andquantitative assays for L-Asparaginase production were determined usingcolorimetric and nesslerization methods respectively. The purification steps involvedialysis of crude extract and DEAE-Cellulose Ion exchange chromatography. Theenzyme was purified 3.39-folds and showed a final specific activity of 0.18 U/mgwith a 41% yield. The crude extract and DEAE-Cellulose fractions showed slightgrowth inhibition against RD cell line (human rhambdomyo sarcoma).